2018
DOI: 10.14419/ijet.v7i3.30.18416
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Macro-Economic Determinants of Real Estate Price in Nigeria

Abstract: Understanding  the relationship between real estate price and macroeconomic  variables in developed countries is appreciated first by considering the housing role in the macro economy. In modern capitalist economy, real estate sector remains the most important element of aggregate demand. Since residential real estate comprises the bulk of country’s tangible capital, the study on relationship between residential real estate price and macro economic variables are very significant for formulation of social and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…With respect to the results, a one percent rise in real income increased housing market prices in China by 0.441% in the near term and 0.343% in the long run. These results are related to Abubakar Alkali et al (2018), who investigated the association of macroeconomic variables, including gross domestic product, with residential prices in Nigeria. He presented that GDP has a positive and significant effect on determining the price of residential property.…”
Section: Housing Market In Chinamentioning
confidence: 72%
“…With respect to the results, a one percent rise in real income increased housing market prices in China by 0.441% in the near term and 0.343% in the long run. These results are related to Abubakar Alkali et al (2018), who investigated the association of macroeconomic variables, including gross domestic product, with residential prices in Nigeria. He presented that GDP has a positive and significant effect on determining the price of residential property.…”
Section: Housing Market In Chinamentioning
confidence: 72%
“…The results from Table 3 below reveal that the during the first cycle, the recovery phase (a) (Remoy et al , 2019; Canepa et al , 2020; Huang, 2019; Alkali et al , 2018; Clayton, 2020; Roulac, 2020, Barras, 2007; Locurcio et al , 2020; Wang and Croucher, 2021; Wisniewski and Brzezicka, 2021; Harnos, 2018; De Stefani, 2021; Pai and Wang, 2020; Jakimowicz and Kulesza, 2017; Grum and Govekar, 2015; Bednarek et al , 2021; Duca et al , 2021; Toledano, 2019) had a total of 3,215 properties transferred, and valuing to a total of P620,708,121.6. Expansion phase (a) had a total of 3,557 properties transferred and with a total value of P2,312,546,275; oversupply phase (a) consisted of a total count of 2,261 properties transferred and a total value of P4,161,698,812.00.…”
Section: Resultsmentioning
confidence: 99%
“…The study showed that housing prices are closely related to business cycle and there is a close relationship between financial cycles and the housing market cycles (Canepa et al , 2020). In addition, a study on macro-economic determinants of real estate price in Nigeria showed that there is a close relationship between real estate residential price and macroeconomic variables in the Nigerian economy (Alkali et al , 2018; Jakimowicz and Kulesza, 2017). Therefore, the impacts of these real estate cycles should not be ignored or oversimplified due to their impacts on property values.…”
Section: Introduction and Background Of The Studymentioning
confidence: 99%
“…Supply and demand in the real estate market can be seen as determinants of housing price. Supply of housing is negatively correlated with the interest rate [8]. As the early investment stage of real estate development is essential in the market, most of the investors gain loans from banks, in this case as soon as the interest rate increases, costs will push upwards.…”
Section: Housing Price and Interest Ratementioning
confidence: 99%